Pengaruh Ukuran KAP, Kepemilikan Manajerial dan Pertumbuhan Perusahaan terhadap Manajemen Laba - Valencia Pangesti; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of public accounting firm size, managerial ownership and growth on earning management. This type of research is causal associative with a quantitative approach. The data used is obtained from the annual reports of companies that performed well during the Covid-19 pandemic listed on the Indonesian Stock Exchange 2018-2021. The sample selection method using purposive sampling obtained 102 samples from 42 companies. This study uses multiple linear regression analysis to test the hypothesis which is assisted by using the SPSS 25 program. The results show that public accounting firm size and managerial ownership don't have a significant on earning management while growth have a positive and significant effect on earning management.